Chemodynamics of barred galaxies in cosmological simulations: On the Milky Way's quiescent merger history and in-situ bulge. Issue 4 (29th April 2020) - Fragkoudi, F; Grand, R J J; Pakmor, R; Blázquez-Calero, G; Gargiulo, I; Gomez, F; Marinacci, F; Monachesi, A; Ness, M K; Perez, I; Tissera, P; White, S D M
ABSTRACT: We explore the chemodynamical properties of a sample of barred galaxies in the Auriga magnetohydrodynamical cosmological zoom-in simulations, which form boxy/peanut (b/p) bulges, and compare these to the Milky Way (MW). We show that the Auriga galaxies which best reproduce the chemodynamical properties of stellar populations in the MW bulge have quiescent merger histories since redshift z ∼ 3.5: their last major merger occurs at t_lookback12 Gyr, while subsequent mergers have a stellar mass ratio of ≤1:20, suggesting an upper limit of a few per cent for the mass ratio of the recently proposed Gaia Sausage/Enceladus merger. These Auriga MW-analogues have a negligible fraction of ex-situ stars in the b/p region (1 per cent ), with flattened, thick disc-like metal-poor stellar populations. The average fraction of ex-situ stars in the central regions of all Auriga galaxies with b/p's is 3 per cent – significantly lower than in those which do not host a b/p or a bar. While the central regions of these barred galaxies contain the oldest populations, they also have stars younger than 5 Gyr (>30 per cent) and exhibit X-shaped age and abundance distributions. Examining the discs in our sample, we find that in some cases a star-forming ring forms around the bar, which alters the metallicity of the inner regions of the galaxy. Further out in the disc, bar-induced resonances lead to metal-rich ridges in the V ϕ − r plane – the longest of which is due to the Outer Lindblad Resonance. Our results suggest the Milky Way has an uncommonly quiet merger history, which leads to an essentially in-situ bulge, and highlight the significant effects the bar can have on the surrounding disc.